An Efficient Algorithm for Generating Maximal Interval Groups in Interval Databases - Arman, Nabil (My University, 2004)
The development of efficient algorithms to enumerate all intervals that have certain properties has attracted a large amount of research efforts due to the important role of interval-based reasoning in different areas like rule-based systems, including Expert Systems (ESs), Information Distribution Systems (IDSs), and database systems to name a few. These algorithms are very crucial to answer certain queries about these intervals. This paper presents an efficient algorithm to generate all maximal interval groups form a given interval set.
Keywords: Maximal interval groups; interval database.